Construction and validation of a scale to measure attitudes towards feral pigeons in college students - Conto Escobar, Karina (2020)
A Likert Scale to measure attitudes towards feral pigeons was developed and evidence regarding reliability and validity was gathered to support its use in psychological and educational research. The validity of the Scale was evaluated by means of expert judges, and Aiken’s V Coefficient values higher than 0.8 were obtained. The reliability was evaluated by means of internal consistency method, applying the Scale to a sample of students from “Universidad Nacional Mayor de San Marcos”, and Cronbach’s Alpha Coefficient values higher than 0.8 were obtained for the total scale and the cognitive, affective, and conative sub scales. In conclusion, the 44 item Scale is a valid an reliable instrument to evaluate university student’s attitudes.